Effect of tolerance to Septoria tritici blotch on grain yield, yield components and grain quality in Argentinean wheat cultivars. (December 2016) - Castro, Ana Carolina; Simón, María Rosa
Abstract: Septoria tritici blotch (STB) caused by Zymoseptoria tritici ( Mycosphaerella graminicola ) is a major disease of wheat worldwide due to significant losses in grain yield and quality. Disease tolerance is the ability to maintain yield performance in the presence of disease symptoms. Therefore, it could be a useful tool in the management of the disease. Although it is known, that there is disease tolerance to STB in some wheat cultivars, this aspect has not been studied among Argentinean cultivars. The aims of this study were to evaluate genotypic differences in tolerance to STB among Argentinean cultivars, considering the relationship between the area under disease progress curve or the green leaf area or the non-green leaf area duration with the grain yield. In addition the effect of the disease on yield, yield components, test weight, grain protein concentration, wet and dry gluten concentration and the influence of tolerance on these traits was investigated. Field experiments were carried out with ten cultivars in a split-split-plot design during 2010 and 2011. Inoculation treatments were the main plots and cultivars, the subplots. STB significantly reduced grain yield, their components, test weight and increase grain protein and gluten concentration. Cultivar Baguette 10 showed major tolerance to STB, indicated by a consistent low regression slope between the green area duration and yield, while Klein Chaja was non-tolerant due to a high regression slope. However, many cultivars such as Buck Brasil, Buck 75 Aniversario, Klein Escorpion and Klein Flecha had considerably similar regression slopes to Baguette 10, provided good levels of tolerance. Other cultivars presented no significant differences. The correlation coefficient between tolerance and grain yield potential was not significant, suggesting that tolerant high-yielding cultivars can be obtained. No relationship was found between quality group or tolerance with the increase in protein and gluten concentration due to STB either. Highlights: Tolerance to STB has been identified among Argentinean wheat cultivars. STB reduced grain yield and their components; increased grain protein and gluten concentration. Tolerant high-yielding cultivars can be obtained. Increase in protein or gluten concentration due to STB was not related with tolerance or wheat quality group.